1995
DOI: 10.1111/j.1464-410x.1995.tb07426.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, ethnicity and geographical location on impotence and quality of life

Abstract: This study indicates that impotent men have a lower quality of life than potent men and has confirmed previous findings that age is associated with impotence. Surprisingly, answers to impotence questions were also associated with geographical location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
95
1
10

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(115 citation statements)
references
References 8 publications
9
95
1
10
Order By: Relevance
“…While some researchers have examined the relationship of marital status and mortality in prostate cancer, 17±18 none has addressed the effect of marital status on HRQOL outcomes. Furthermore, few studies have speci®cally addressed the effect of age 19 or insurance status on quality of life outcomes in prostate cancer. This study was designed to examine whether these and other sociodemographic and clinical variables are predictive of HRQOL outcomes in prostate cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers have examined the relationship of marital status and mortality in prostate cancer, 17±18 none has addressed the effect of marital status on HRQOL outcomes. Furthermore, few studies have speci®cally addressed the effect of age 19 or insurance status on quality of life outcomes in prostate cancer. This study was designed to examine whether these and other sociodemographic and clinical variables are predictive of HRQOL outcomes in prostate cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Age is an important factor to examine as it has a strong correlation with ED and can affect the rate of ED in a survey [2,4]. The strati®ed prevalence of ED by age is often omitted in studies or made unreliable because there are too few subjects in each of the age ranges [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Our estimated response rate of 64.8% and participation rate of 88% are comparable to other studies. 2,3,11,15,16 Diokno et al 9 found that 73.8% married men above the age of 60 y were still sexually active. In the age group 60±69 y, Keil et al 17 reported that 70% were sexually active.…”
Section: Discussionmentioning
confidence: 99%